2015
DOI: 10.1186/s13104-015-1348-9
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s sarcoma: a 10-year experience with 248 patients at a single tertiary care hospital in Tanzania

Abstract: BackgroundKaposi’s Sarcoma is the most common sarcoma and second most prevalent cancer seen in Tanzania. Little is known about Kaposi’s sarcoma in our setting as there is paucity of recent published data regarding this condition. This study describes the clinicopathological pattern and treatment outcome of Kaposi’s sarcoma at Bugando Medical Centre, a tertiary care hospital in northwestern Tanzania.MethodsThis was a prospective study of histologically confirmed Kaposi’s sarcoma that was conducted at Bugando Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
33
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 54 publications
(99 reference statements)
16
33
4
Order By: Relevance
“…On the other hand, we found that affected women were significantly younger than affected men (34.7 vs. 40.4 years; p < 0.001); this result is similar to findings from Enow Orock et al [14] (36.1 vs. 42.4 years) and from Chalya et al [16] (28 vs. 37 years). This might be because the women probably got infected by HIV at a younger age than the men; furthermore, the immunosuppression caused by HIV infection and KS's pathogenesis may progress more rapidly in women than in men [16]. It is worth highlighting that the majority were young adults, with 76.3% of the patients aged less than 45 years.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…On the other hand, we found that affected women were significantly younger than affected men (34.7 vs. 40.4 years; p < 0.001); this result is similar to findings from Enow Orock et al [14] (36.1 vs. 42.4 years) and from Chalya et al [16] (28 vs. 37 years). This might be because the women probably got infected by HIV at a younger age than the men; furthermore, the immunosuppression caused by HIV infection and KS's pathogenesis may progress more rapidly in women than in men [16]. It is worth highlighting that the majority were young adults, with 76.3% of the patients aged less than 45 years.…”
Section: Discussionsupporting
confidence: 91%
“…This difference could be explained by the fact that the latter studies considered both patients affected by endemic KS and those affected by epidemic KS, endemic KS being more frequent among men [3,20]. On the other hand, we found that affected women were significantly younger than affected men (34.7 vs. 40.4 years; p < 0.001); this result is similar to findings from Enow Orock et al [14] (36.1 vs. 42.4 years) and from Chalya et al [16] (28 vs. 37 years). This might be because the women probably got infected by HIV at a younger age than the men; furthermore, the immunosuppression caused by HIV infection and KS's pathogenesis may progress more rapidly in women than in men [16].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations